2020
DOI: 10.1039/d0tc02516j
|View full text |Cite
|
Sign up to set email alerts
|

Enhancement of thermal stability and energy storage capability of flexible Ag nanodot/polyimide nanocomposite filmsvia in situsynthesis

Abstract: High-temperature electrostatic capacitors are in urgent demand owing to the rapidly development of advanced power electronic applications. However, polymer films with favorable discharge energy density and efficiency are still a...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
19
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 36 publications
(19 citation statements)
references
References 56 publications
0
19
0
Order By: Relevance
“…[1][2][3][4][5] Electrostatic capacitors possess the highest power densities, i.e., up to 10 7 -10 8 High-temperature polymers, including polyimide (PI), polyetherimides (PEI), polycarbonate (PC), fluorene polyester (FPE), and poly(ether ether ketone) (PEEK), have been examined as polymer dielectrics owing to their high glass transition temperatures (T g ) and excellent thermal stability. [9,13,[19][20][21][22][23][24][25][26][27] However, as the electrical conduction increases exponentially with the increase of temperature and the applied electric field, high energy loss and large reductions in η, and discharged energy density (U e ) are found in the polymers at temperatures even well below their T g . [28][29][30] For instance, U e and η of Kapton PI with a T g of ≈360 °C drop precipitately from 1.53 J cm −3 and 95.2% at room temperature to 0.82 J cm −3 and 55.7%, respectively, as temperature rises to 150 °C.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4][5] Electrostatic capacitors possess the highest power densities, i.e., up to 10 7 -10 8 High-temperature polymers, including polyimide (PI), polyetherimides (PEI), polycarbonate (PC), fluorene polyester (FPE), and poly(ether ether ketone) (PEEK), have been examined as polymer dielectrics owing to their high glass transition temperatures (T g ) and excellent thermal stability. [9,13,[19][20][21][22][23][24][25][26][27] However, as the electrical conduction increases exponentially with the increase of temperature and the applied electric field, high energy loss and large reductions in η, and discharged energy density (U e ) are found in the polymers at temperatures even well below their T g . [28][29][30] For instance, U e and η of Kapton PI with a T g of ≈360 °C drop precipitately from 1.53 J cm −3 and 95.2% at room temperature to 0.82 J cm −3 and 55.7%, respectively, as temperature rises to 150 °C.…”
Section: Introductionmentioning
confidence: 99%
“…S14. † 7,12,13,18,19,26,33,[39][40][41][42][43][44][45][46][47] For instance, the maximum U e values of PEI/BTNP/BNNS, A-P-A-P-A, BT-BCB@DPAES(D), PEI/STNPs, XL-VK-2, c-BCB/Al 2 O 3 NPLs, and PEI/Al 2 O 3 @ZrO 2 were 2.92, 3.00, 3.10, 3.18, 3.95, 4.10, and 5.15 J cm À3 at 150 C, respectively, 7,13,18,41,[44][45][46] which were less than those obtained in this study. Furthermore, it must be emphasized that, compared to highly doped nanocomposites, nanocomposites with low llings have great potential and benet from less introduction of interfacial defects and agglomerates.…”
Section: Resultsmentioning
confidence: 99%
“…[28][29][30][31] Several studies have revealed that conductor llers with ultralow loading contents can improve the breakdown strength (E b ) and U e of polymer lms. [32][33][34][35] For instance, Shen et al enhanced the dielectric constant ($50%) and breakdown strength ($15%) by synthesizing trace Ag nanodots (0.05 vol%) in a poly(vinylidene uoride-hexauoropropylene) matrix, resulting in an improved room temperature (RT) discharged energy density owing to the Coulomb blockade effect. 32 In comparison with semiconductors and insulating nanollers, ultrane metal nanoparticles can effectively enhance E b and maintain a low dielectric loss of polymers at a low ller loading by utilizing their unique small size and Coulomb blockade effects.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…For comparison, the U d and η of previously reported representative monolayer composites are summarized in Figure . ,,,, In brief, the red part presents high energy density, while the blue part presents high efficiency. Hence, the optimal energy storage properties of composites ought to be presented in the direction of the green arrow.…”
Section: Resultsmentioning
confidence: 99%